Zero discharge: Pilot project for biodegradation of cattle effluent by pyroclastic "lapilli" treatment for fodder irrigation. (1st February 2019) - Mendoza-Grimón, V.; Fernández-Vera, J.R.; Hernández-Moreno, J.M.; Hernández-Brito, I.; Palacios-Diaz, M.P.
Abstract: Livestock effluents are a nutrient supply that is beneficial for crops, so their use is essential to guarantee the sustainability of the global management of farms. Zero discharge cattle effluent management to irrigate fodder crops is a mitigation option, so it is considered a key factor for adaptation to climate change. This paper presents the result of an "on site" pilot scale (three-stage, vertical flow filtration system using lapilli). This is a low-cost solution in terms of finance and energy, which does not require the addition of chemicals, to treat a cattle effluent. The effluent's quality obtained allowed it to be injected in a drip system with low risks of obstruction. And the pilot system allowed to obtain elimination values for the main parameters of effluent's quality (TSS and COD, 98% and 80% respectively) similar or greater than the ones obtained in other treatments of low cost and energy, and gives values contemplated in reclaimed water reuse guidelines of many countries. Furthermore, elimination rate for the BOD5 obtained 35 mgL −1 in treated effluent. High removal rates were obtained for N, P, K, Cu, Fe and Mn, medium for Ca, Mg and Zn and low for B and Na. These shows that the pilot system and fodder crop combination provide an optimal solution to small farms, controlling sanitary risks. The tested flow allows the use of this system by conventional small farms, which represented 94% of total cow farms in Canary Islands. Highlights: An alternative for effluent treatment using lapilli filtration to irrigate forages. A climatic mitigation option obtaining a zero discharge cattle effluent management. 98% & 80%, TSS & COD elimination, similar than obtained in other low cost treatments. Treated effluent (35 mgL −1 DBO5 ) suitable by the restricted irrigation guidelines. To obtain high removal rates (N, P, K, Cu, Fe, Mn) medium (Ca, Mg, Zn) & low (B, Na).